2018
DOI: 10.1021/acsphotonics.8b00151
|View full text |Cite
|
Sign up to set email alerts
|

Giant Field Enhancements in Ultrathin Nanoslots above 1 Terahertz

Abstract: Strong demand for plasmonic devices with an enormously enhanced electric field and desired resonance frequencies has led to extensive investigations of metallic slot structures. While strong field enhancement can be achieved by reducing the width of the slot, the effect of the gap surface plasmon limits the maximum achievable field enhancement at higher frequencies. Specifically, the effect of the gap surface plasmon becomes stronger as the gap width decreases and strongly suppresses the transmission while cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…Metallic nano‐trenches, or nano‐slots, are a viable solution to solving this issue, as fine tuning of the gap width leads to a very large change in the optical properties of the sample due to gap plasmon modes within the gap. [ 21–23 ] Most importantly, in these structures the gap width and the operating wavelengths are completely decoupled, which means that changing the gap width by a few nanometers can significantly change the optical properties of the slits or slots operating at millimeter or longer wavelengths. This has been partially demonstrated in active slot antennas where gap widths modulated from 5 to 2 nm by thermal expansion of metallic films caused 30% modulation of transmitted terahertz waves.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic nano‐trenches, or nano‐slots, are a viable solution to solving this issue, as fine tuning of the gap width leads to a very large change in the optical properties of the sample due to gap plasmon modes within the gap. [ 21–23 ] Most importantly, in these structures the gap width and the operating wavelengths are completely decoupled, which means that changing the gap width by a few nanometers can significantly change the optical properties of the slits or slots operating at millimeter or longer wavelengths. This has been partially demonstrated in active slot antennas where gap widths modulated from 5 to 2 nm by thermal expansion of metallic films caused 30% modulation of transmitted terahertz waves.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the gap-filling dielectric has been removed successfully without any apparent damage to the nano-trenches, leading to a decrease in the permittivity inside the gap and a subsequent decrease in effective indices within the gap. Figure 4b shows the theoretical spectra calculated with the coupled mode method [31,32], which have been successfully implemented in simulating nanostructures in long-wavelength regimes [33][34][35]. We modeled collapsing of the gap as an increase in imaginary permittivity of the gap material, i.e., an increase in conductivity, due to formation of metallic bridges in the gap.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 b shows the theoretical spectra calculated with the coupled mode method [ 31 , 32 ], which have been successfully implemented in simulating nanostructures in long-wavelength regimes [ 33 , 34 , 35 ]. We modeled collapsing of the gap as an increase in imaginary permittivity of the gap material, i.e., an increase in conductivity, due to formation of metallic bridges in the gap.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the thickness of devices has become even thinner. In case of ten-nanometer-thick devices, our previous work 7 has demonstrated that performance, e.g., field enhancement, of nano-plasmonic devices, is increased by 6-fold, compared to a hundred-nanometer-thick devices. Hence, fabrication and comprehensive investigation of optical properties of ultra-thin gold film are promising as well as essential.…”
Section: Introductionmentioning
confidence: 99%